Neuromuscular training and motor control in youth athletes: A meta-analysis - Williams, M. D.; Ramirez-Campillo, R.; Chaabene, H.; Moran, J. (Perceptual and Motor Skills, 2021)
Our purpose in this review was to determine the effects of bodyweight-only neuromuscular training (NMT) programs on motor control of movement among youth athletes. We searched three electronic databases (CrossRef, Google Scholar, and PubMed), using the following inclusion criteria for selecting research studies: (a) healthy male and female participants aged 8-18 years who were engaged in organized sports; (b) interventions up to 16-weeks duration; (c) incorporation of a control group; and (d) interventions that utilized only exercises using participants` body mass. We calculated pooled estimates of effect sizes (standardized mean difference) for changes in motor control across nine studies (12 comparisons) using the inverse-variance random effects model for meta-analyses and 95% confidence intervals. Among the nine studies included in our meta-analysis, there was a moderate, significant effect in favor of neuromuscular training programs (0.79 [95% CI: 0.38, 1.20], Z = 3.76 [p = 0.0002]) on motor control. Heterogeneity was high and significant (I2= 77% [p = 0.00001]). Moderator analyses for age and stature revealed NMT programs to be more effective in younger, shorter, and lighter individuals. We found larger effect sizes in males, and for programs >8 weeks in duration. We concluded that the older and heavier an individual is, the less effective bodyweight-only NMT programs became, particularly for female participants. These results reinforce the notion that exercise to enhance motor control should be emphasized during pre-adolescence.